2009
DOI: 10.1016/j.biocon.2008.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Distance to edges, edge contrast and landscape fragmentation: Interactions affecting farmland birds around forest plantations

Abstract: Clustering forest plantations in a few large patches and thus reducing the density of wooded edges at the landscape-scale might reduce such negative impacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
136
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(157 citation statements)
references
References 44 publications
(83 reference statements)
15
136
1
2
Order By: Relevance
“…This guild is associated with scattered montados and to agricultural edges, decreasing its densities with the proximity of forested edges, like eucalyptus or pine plantations. Such tendency was also recorded by Reino et al (2009) with the same group of species but in a farmland context. According to such relations between birds and habitat, the farmland species occurring in montados can be defined as generalist farmland species.…”
Section: Discussionsupporting
confidence: 65%
“…This guild is associated with scattered montados and to agricultural edges, decreasing its densities with the proximity of forested edges, like eucalyptus or pine plantations. Such tendency was also recorded by Reino et al (2009) with the same group of species but in a farmland context. According to such relations between birds and habitat, the farmland species occurring in montados can be defined as generalist farmland species.…”
Section: Discussionsupporting
confidence: 65%
“…Our results also showed that borders between the focal patch and commercial plantations of E. globulus and P. radiata exhibited high-contrast habitat edges, due to substantial differences in terms of tree height and richness of tree and shrub species. Previous studies have also reported that mono-specific plantations of Eucalyptus may exhibit high-contrast edges with natural habitat due to a more simple composition and structure (Reino et al 2009). …”
Section: Discussionmentioning
confidence: 96%
“…Priority sites for restoration were considered those patches with an ECON greater than 50 (ECON >50 means that more than 50% of the focal habitat edge has high contrast with its neighborhood in terms of demonstrated that the proposed restoration of high-contrast sites dissecting the focal habitat may cause an increase in the extensiveness of the focal habitat; specifically, the restoration of edges bounded by commercial plantations of P. radiata and Eucalypts which may have negative effects on species assemblages (Bustamante & Simonetti 2005;Reino et al 2009). …”
Section: Prioritization Of Restoration Sitesmentioning
confidence: 99%
“…In contrast, landscape contrast has been considered as a crucial factor for assessing habitat pattern across different scales (Biswas andWagner 2012, Schindler et al 2008). Edge contrast affected the magnitude of edge effects, with a tendency for stronger responses to old and tall plantations (hard edges) than to young and short plantations (soft edges) (Reino et al 2009). For example, in the form of passive dispersal, seeds will accumulate on the forest boundary as plants dispersed by wind; or the "terrain barriers" can act as obstacles for the movement of certain species.…”
Section: Introductionmentioning
confidence: 99%